Pengawasan Internal terhadap Tindakan Koruptif Pejabat Pemerintahan Daerah oleh Aparatur Pengawasan Intern Pemerintahan (Studi Kasus Pemerasan Kepala Dinas Provinsi Bengkulu) - Vianka, Tania; Wati, Linda; Adzkia, Nurul; Susanti, Pipi (Indonesian Journal of Law and Justice, 2025)
This study aims to evaluate the effectiveness of internal supervision conducted by the Government Internal Supervisory Apparatus (APIP), particularly the Regional Inspectorate, in preventing and addressing corruption within local governments. The research uses a normative juridical approach by analyzing laws and regulations, combined with case studies specifically, extortion practices within the Bengkulu Provincial Government. The findings reveal that internal supervision has not functioned optimally. Several factors contribute to this ineffectiveness, including the failure of the internal control system, limited independence of the Government Internal Supervisory Apparatus (APIP), and insufficient coordination with external oversight bodies. These issues suggest that the current internal supervision mechanism remains vulnerable to political intervention and is inadequate in detecting or preventing structural corruption. In practice, the Government Internal Supervisory Apparatus (APIP) often lacks the authority and resources necessary to carry out thorough and independent investigations, especially in politically sensitive cases. To address these shortcomings, the study recommends a series of reforms. These include strengthening the institutional position and independence of the Government Internal Supervisory Apparatus (APIP), revising and updating technical regulations related to the Government Internal Control System (SPIP), and enhancing coordination and information-sharing between internal and external supervisory institutions. A more empowered and independent the Government Internal Supervisory Apparatus (APIP) would be better equipped to uphold integrity, transparency, and accountability in local governance. In conclusion, comprehensive improvements in internal supervision are essential to support anti-corruption efforts and ensure good governance at the regional level. Strengthening internal control is not only a legal necessity but also a strategic step toward building public trust in government institutions.